TGF-β signaling in Th17 cells promotes IL-22 production and colitis-associated colon cancer - Laura Garcia Perez (Nature Portfolio, 2020)
Poly-functional helper T cells can have a stronger effect than mono-functional T cells, but whether the response is qualitatively different is not clear. Here the authors show that a population of IL-17+IL-22+, but not single IL-22+, CD4+ T cells are induced by TGF-β, enriched in patients with colorectal cancer (CRC) and drive CRC progression in mice.